A Bimolecular Fluorescence Complementation Tool for Identification of Protein-Protein Interactions in Candida albicans. Issue 10 (1st October 2017) - Subotić, Ana; Swinnen, Erwin; Demuyser, Liesbeth; De Keersmaecker, Herlinde; Mizuno, Hideaki; Tournu, Hélène; Van Dijck, Patrick
Abstract: Investigation of protein-protein interactions (PPI) in Candida albicans is essential for understanding the regulation of the signal transduction network that triggers its pathogenic lifestyle. Unique features of C. albicans, such as its alternative codon usage and incomplete meiosis, have enforced the optimization of standard genetic methods as well as development of novel approaches. Since the existing methods for detection of PPI are limited for direct visualization of the interacting complex in vivo, we have established a bimolecular fluorescence complementation (BiFC) assay in C. albicans, a powerful technique for studying PPI. We have developed an optimized set of plasmids that allows for N- and C-terminal tagging of proteins with split yeast-enhanced monomeric Venus fragments, so that all eight combinations of fusion orientations can be analyzed. With the use of our BiFC assay we demonstrate three interaction complexes in vivo, which were also confirmed by two-hybrid analysis. Our Candida -optimized BiFC assay represents a useful molecular tool for PPI studies and shows great promise in expanding our knowledge of molecular mechanisms of protein functions.